Food networks in the North American Arctic. - Duhaime, Gérard; Morin, Alexandre; Myers, Reather; Caulfield, Rickard A.; Fréchette, Pierre; St-Pierre, Dominique (University of Alberta, CCI Press & GÉTIC, 2024)
This chapter presents the state of our knowledge about the formal economy of food security in the Arctic. It explains the main characteristics of food markets in different Arctic regions, and addresses such questions as: what businesses are involved (private, public, local, national, international, etc.)? What is the structure of the supply chain (import/export, links from the producers to retail stores)? Is local food sold in the formal market (products of renewable resource exploitation and local manufacture, when available)? Are the food chains well established and reliable, or new and fragile? etc. This is the first time an effort is made to synthesize such issues, usually considered under the single angle of the hunting and fishing production in the Arctic. This work provides solid basis for evaluating this key component of food supply and consumption, even if it concludes that more research has to be done to have a complete picture.